Expression of Some Neural Markers During Subculturing of Native and Cryopreserved Spheroids Derived From Neonatal Porcine Dorsal Root Cells - Ali, Sabina G.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 173.